The wellbeing of siblings of children with disabilities - Giallo, Rebecca; Emerson, Eric (My University, 2014)
The aims of our study were: (1) to estimate the extent of differences in wellbeing between siblings of children with disabilities or long-term health conditions and siblings of ‘typically developing’ children in a nationally representative cohort of Australian children (the Longitudinal Study of Australian Children); (2) to determine whether any between-group differences in wellbeing may be potentially attributable to between-group differences in exposure to socio-economic disadvantage. The results of our analyses were consistent with the existing literature in indicating that, in unadjusted comparisons, the siblings of children with long-term health conditions or disabilities: (1) had lower wellbeing than their peers on some, but not all, indicators of wellbeing; and (2) that where differences did exist the effect sizes were small. Our results add to the existing literature in: (1) indicating that adjusting for between-group differences in exposure to low SEP and associated adversities eliminated the statistical significance of unadjusted comparisons in the majority of instances; and (2) failing to find any evidence of deterioration over time in the wellbeing of siblings with long-term health conditions or disabilities over a two-year period from age 4/5 to age 6/7.
Research in Developmental Disabilities
Keywords: Children -- Disabled; Child Development -- Behaviour; Children -- Infants; Childhood and child development; Children; Child Development; Behaviour; Disabled; Infants; Childhood and child development